The musical effects in the poem of : Emrio‘ Alqays - Mohammed, Ibrahim Abdullah Ibrahim; Fadlallah, Mohamed Abdullah Mohamed; Ahmed, Gamal El Din Ibrahim Abdel Rahman (Journal of Humanities & Social Sciences, 2017)
This study is about the "musical influences in the poem of the poet: Emro Algays , by description, analysis and interpretation, in addition to the grammatical, morphological, linguistic, rhetorical, and rhythmic influences followed by their rhythms , melodies, and their effect in forming the melodic wave in about twenty segments . The descriptive analytical method; is adopted in the study, for it can describe vividly and analyze deeply the different rhythmic phenomena, highlighting the aesthetics of language and artistic images. The end-product of the study unveiled the following fruits: The poet adopted (Bahr al-Tawil II)(one of the Arabic poetry rules made by the linguistic scholar – Alkahleel Bin Ahmed Alfrahidi) to express his deep passionate emotions and his violent adventures in chasing and Fishing .2- The narrators agreed to the authenticity of the poem and did not differ only in four verses .. The poem eloquence percentage arrived at 46%, while the proportion of the mental emotion - according to the theory of Buthee Man - is about 2.39%. 3- The two vowel segments of the poem are equal in all verses of the poem at a rate of (14 segments) for each section. Verse 4 which read as follows: You see the deer’s remains in the space and valleys like peppercorn , this vers is thought to be the most poetic verse for the quietness and pacific tune due to the notions of the of letters. The verse 76 is thought to the most eloquent verses due to the concentration of the letters notion which called (Flashing). As for the verses 14 and 74 are the most eloquent verses. The verse 54 which gives a vivid details to the horse, in all situations, has got a sweetness of the rhythm, the melody and the attraction of the music, the most complete of the songs ,with no dispute on its authenticity.